Long-Term Effects of Exercise on Balance and Fear of Falling in Elderly - Widagdo, The Maria Meiwati; Laurentia, Claudia Bella; Suryadiningrat, Bagus Anggawaisna Anggawaisna; Perdamaian, Teguh Kristian (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
Falls is the main cause of injuries in elderly. Studies on the long-term effects of balance training are still limited. This study aimed to assess the long-term impact of a physical exercise on the balance and fear of falling in community dwelling elderly. This was a quasi-experimental study with pre-post design. The participants were older people ≥60 years with balance problems. They received a one-month physical exercise. The instruments included Functional Reach Test (FRT) to assess balance and Falls Efficacy Scale-International (FES-I) to assess fear for falling. Assessment was conducted at pre- and post-intervention and two years later. Data were analysed using Wilcoxon Signed-Rank Test and linear mixed model regression. Data of 23 participants were analysed. There were significant differences inn FRT and FES-I between pre-and post-intervention, pre-intervention and two years later. There was no significant difference in FRT and FES-I between post-intervention and two years after. There was significant improvement in the balance and fear of falling one month and two years after the program. The balance program had long-term effect that lasted at least for two years. Inclusion of the balance program in community-based health program for elderly can improve balance and prevent falls.